Development of site-specific wind hazard map for peninsular Malaysia via spatial modeling - Sabah, Saddam Hussein Abo; Noram Irwan, Ramli; Taksiah, A. Majid; Shaharudin Shah, Zaini (MDPI AG, 2020)
The commonly used approach to predict and evaluate the wind risk in Peninsular Malaysia is to employ the basic wind speed (Vs) hazard map, which underestimates the real damage due to the limitation of factors considered by the current map. This paper aimed to develop a new wind hazard map for Peninsular Malaysia based on the site wind speed (Vsite) rather than the Vs using the Geographical Information System. The development of the Vsite map considered the effects of the Land Use Land Cover (LULC) and the topography conditions that were not taken into consideration by the Malaysian Standard during the development of the Vs map. The statistical analysis proved that the wind hazard in Peninsular Malaysia is directly proportional to the LULC and inversely proportional to the Hill Shape Multiplier. In addition, the results showed that the existing Vs map underrated the wind hazard in Peninsular Malaysia by almost 9.02% to 17.79% compared to the developed Vsite map. Therefore, the use of the newly developed map to evaluate the wind hazards will significantly enhance the assessment, and the new map has the potential to be incorporated into the Malaysian Standard for this purpose.